The cross-border exercise of the civil reply action - Martínez Calvo, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Despite the initiatives of harmonization that have been carried out from some international forums, the regulation of the right of reply is dispersed in the legal systems of the different States, which have configured it in different ways. This makes the cross-border exercise of the civil reply action difficult and presents some problems for the determination of international jurisdiction and applicable law, since Private International Law does not expressly refer to the right of rectification.